Optimalisasi Proses Bisnis UMKM Kerajinan Gerabah melalui Sinergi Inovasi Pemasaran dan Manajemen Risiko Terstruktur - Jalil, Ivon; Malahayati, Malahayati; Yana, Syaifuddin; Heriyana, Heriyana; Ilyas, Ilyas; Nengsih, Rita (Jurnal Serambi Engineering, 2025)
This study explores the optimisation of business processes through the synergy of marketing innovation and structured risk management, particularly for small and medium-sized enterprises (SMEs). SMEs often face challenges such as limited resources, market uncertainties and fluctuating raw material prices. By integrating marketing innovation with structured risk management, companies can improve operational efficiency and mitigate potential risks, creating a solid foundation for sustainable growth. Marketing innovation, particularly through digital platforms, enables SMEs to expand their market reach, attract new customers and remain competitive. Meanwhile, structured risk management ensures that innovative strategies are implemented safely and effectively. This synergy not only minimises operational and financial losses, but also enables SMEs to adapt to dynamic market conditions. The study highlights the importance of combining process optimisation with strategic innovation to increase productivity, reduce waste and remain competitive in the modern business environment. By adopting this integrated approach, SMEs can achieve long-term profitability and resilience in a rapidly changing economic landscape.